Glechoma hederacea Suppresses RANKL-mediated Osteoclastogenesis. (July 2014) - Hwang, J.K.; Erkhembaatar, M.; Gu, D.R.; Lee, S.H.; Lee, C.H.; Shin, D.M.; Lee, Y.R.; Kim, M.S.
Glechoma hederacea (GH), commonly known as ground-ivy or gill-over-the-ground, has been extensively used in folk remedies for relieving symptoms of inflammatory disorders. However, the molecular mechanisms underlying the therapeutic action of GH are poorly understood. Here, we demonstrate that GH constituents inhibit osteoclastogenesis by abrogating receptor activator of nuclear κ-B ligand (RANKL)-induced free cytosolic Ca 2+ ([Ca 2+ ]i ) oscillations. To evaluate the effect of GH on osteoclastogenesis, we assessed the formation of multi-nucleated cells (MNCs), enzymatic activity of tartrate-resistant acidic phosphatase (TRAP), expression of nuclear factor of activated T-cells cytoplasmic 1 (NFATc1), and [Ca 2+ ]i alterations in response to treatment with GH ethanol extract (GHE) in primarily cultured bone marrow–derived macrophages (BMMs). Treatment of RANKL-stimulated or non-stimulated BMMs with GHE markedly suppressed MNC formation, TRAP activity, and NFATc1 expression in a dose-dependent manner. Additionally, GHE treatment induced a large transient elevation in [Ca 2+ ]i while suppressing RANKL-induced [Ca 2+ ]i oscillations, which are essential for NFATc1 activation. GHE-evoked increase in [Ca 2+ ]i was dependent on extracellular Ca 2+ and was inhibited by 1, 4-dihydropyridine (DHP), inhibitor of voltage-gated Ca 2+ channels (VGCCs), but was independent of store-operated Ca 2+ channels. Notably, after transient [Ca 2+ ] elevation, treatment with GHE desensitized the VGCCs, resulting in an abrogation of RANKL-induced [Ca 2+ ]i oscillations and MNC formation. These findings demonstrate that treatment of BMMs with GHE suppresses RANKL-mediated osteoclastogenesis by activating and then desensitizing DHP-sensitive VGCCs, suggesting potential applications of GH in the treatment of bone disorders, such as periodontitis, osteoporosis, and rheumatoid arthritis.